Development of Scaffold for Tissue Engineering Application using Imprinting - N., Vigneswaran; Fahmi, Samsuri; Nithya, Kalyani K. (2014)
In this article we report the development of scaffold mimicking the cell surface topography. Using Soft lithography, in which polymer (triglyme, ethylene glycol dimethacrylate, methacrylic acid and IRGAcure 2022) is applied over the cultured cell and cured instantly using UV source. IRGA cure 2022 is photoinitiator, which helps in solidification of the polymer when exposed to UV light source. Triglyme helps to increase the viscosity of the polymer. This method can be applied to alladherent cells. This scaffold consist of cell surface topography features. The development scaffold can pave way in tissue engineering for various applications and cell research investigations.